Analyzing the Price Gap Between Steers and Bulls in Florida: The Effect of Price Slides on the Value of Additional Pounds - Hannah Baker (EDIS, 2024)
Castration of bull calves on cow-calf operations usually improves profitability. On average over the last six years, Florida prices for steer calves have been 5% higher than prices for bull calves. In 2023, a year of record-high prices, steer prices averaged 6% higher, with the average discount for bulls at roughly $64 per head. Buyers pay more for steer calves because they are docile, and because steer carcasses are more valuable. Cattle producers are therefore encouraged to castrate bull calves. Bulls may weigh more than steers at the time of weaning, bringing what seems like a higher price, but there is a price slide for entering the heavier weight class. Determining the value of those additional pounds, and whether it is enough to make up for the discount is key. Using prices from 2023 (with prices projected to remain favorable for at least the next year), this publication allows producers to determine what a bull calf would need to weigh to receive the same price as a steer calf.